A different shade of colonialism : Egypt, Great Britain, and the mastery of the Sudan - Powell, Eve Troutt (Berkeley : University of California Press, 2003)
This incisive study adds a new dimension to discussions of Egypt's nationalist response to the phenomenon of colonialism as well as to discussions of colonialism and nationalism in general. Eve M. Troutt Powell challenges many accepted tenets of the binary relationship between European empires and non-European colonies by examining the triangle of colonialism marked by Great Britain, Egypt, and the Sudan.
Journeys from the fantastic to the colonial -- Black servants and saviors : the domestic empire of Egypt -- The lived experience of contradiction : Ibrahīm Fawzī's narrative of the Sudan -- The tools of the master : slavery, family, and the unity of the Nile Valley -- Egyptians in blackface : revolution and popular culture, World War I to 1925.
Includes bibliographical references (pages 241-250) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Egypt -- Relations -- Sudan; Sudan -- Relations -- Egypt; Egypt -- History -- 19th century; Sudan -- History -- 19th century; Slavery -- Egypt -- History -- 19th century; Slavery -- Sudan -- History -- 19th century; Égypte -- Histoire -- 19e siècle.; Soudan -- Histoire -- 19e siècle.; POLITICAL SCIENCE -- Colonialism & Post-Colonialism.; HISTORY -- Middle East -- General; International relations; Slavery; Egypt; Sudan; 1800-1899; History